Fault location method combining transient mutation and dynamic time warping algorithm for grounding system. (March 2023) - Liu, Kangli; Zhang, Chi; Chen, Wenzhe; Zhao, Jianfeng
Abstract: In the urban distribution network, due to the wide application of underground cables, the traditional resonant grounding system has gradually been unable to match the increasing fault current amplitude, real-time compensation and harmonic component compensation requirements. With the continuous advancement of reliable power electronics technology, flexible grounding systems (FGS) based on controllable converters are receiving more attention. Whether it is a traditional grounding system or a flexible grounding system, when a single-phase grounding fault occurs in the power grid, in order to ensure the safety of the power grid, it is necessary to accurately locate the fault in the system. However, how to apply traditional location methods to flexible grounding systems and high-resistance grounding faults is a challenge. In this paper, a new fault location method combining transient mutation and dynamic time warping (DTW) algorithm is proposed. The transient mutation is detected and used for the primary selection of the fault interval firstly. And then, the dynamic time warping algorithm determines the difference between the intervals, and the specific fault location is finally calculated and identified. The verification results based on MATLAB/Simulink prove the rationality and effectiveness of the proposed method.